Megalithic Culture In Suboh Sub District Situbondo Regency - Handoko, Nurcholis Fitrio; Swastika, Kayan; Na'im, Mohamad; Pratama, Akhmad Ryan; Puja, Gusti Ngurah Ary Kesuma; Jamil, Robit Nurul (JURNAL HISTORICA, 2023)
The megalithic culture in Suboh District, Situbondo Regency has its own uniqueness, namely the mortar stones, where the mortar stones in Suboh District have holes around the main hole, where the holes function to place crushed grain and there are also many archaeological remains that have not been recorded. The aim of this research is to add to the inventory of archaeological remains, social, economic and cultural systems. The type of research is qualitative research. The research methods are: (1) heuristics, (2) criticism, (3) interpretation, (4) historiography. Based on the research results, the typology of archaeological remains in Suboh District consists of three types, namely sarcophagi, stone mortars and stone monoliths with a hollow stone type. Community supporters of megalithic culture in Suboh District already know the concept of belief in the spirits of ancestors (acestor-worship). Social, economic and cultural life has recognized an egalitarian agricultural system. Keywords: Culture, Suboh, Megalithic